Evaluation of one of leading Indonesia’s digital wallet using the unified theory of acceptance and use of technology - Natalia Limantara; Jevan Jovandy; Anindya Khansalihara Wardhana; Steven Steven; Fredy Jingga (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The goal of this research is to assess the utilization of one of Indonesia's most popular digital wallets. Respondents in this study range in age from 15 to 44 years old and live on Java Island. The author employs the unified theory of acceptance and utilization of technology (UTAUT) paradigm to assess the use of this digital wallet. This UTAUT model comprises four latent variables that affect behavioral intention (BI) and use behavior (UB): performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC). In this study, the UTAUT model is combined with two additional variables: perceived risk (PR) and promotional benefits (PB). According to the findings, performance expectancy, social influence, and perceived risk all have an impact on behavioral intention, whereas effort expectancy has a less impact. Furthermore, the factors facilitating conditions and promotional benefits have a minor impact on use behavior, whereas behavioral intention factors have a considerable impact on use behavior.